**Answer:**

X=15

**Step-by-step explanation:**

4*x/3+3-(23)=0

Step by step solution :

STEP

1

:

x

Simplify —

3

Equation at the end of step

1

:

x

((4 • —) + 3) - 23 = 0

3

STEP

2

:

Rewriting the whole as an Equivalent Fraction

2.1 Adding a whole to a fraction

Rewrite the whole as a fraction using 3 as the denominator :

3 3 • 3

3 = — = —————

1 3

Equivalent fraction : The fraction thus generated looks different but has the same value as the whole

Common denominator : The equivalent fraction and the other fraction involved in the calculation share the same denominator

Adding fractions that have a common denominator :

2.2 Adding up the two equivalent fractions

Add the two equivalent fractions which now have a common denominator

Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:

4x + 3 • 3 4x + 9

—————————— = ——————

3 3

Equation at the end of step

2

:

(4x + 9)

———————— - 23 = 0

3

STEP

3

:

Rewriting the whole as an Equivalent Fraction :

3.1 Subtracting a whole from a fraction

Rewrite the whole as a fraction using 3 as the denominator :

23 23 • 3

23 = —— = ——————

1 3

Adding fractions that have a common denominator :

3.2 Adding up the two equivalent fractions

(4x+9) - (23 • 3) 4x - 60

————————————————— = ———————

3 3

STEP

4

:

Pulling out like terms :

4.1 Pull out like factors :

4x - 60 = 4 • (x - 15)

Equation at the end of step

4

:

4 • (x - 15)

———————————— = 0

3

4*x/3+3-(23)=0

Step by step solution :

STEP

1

:

x

Simplify —

3

Equation at the end of step

1

:

x

((4 • —) + 3) - 23 = 0

3

STEP

2

:

Rewriting the whole as an Equivalent Fraction

2.1 Adding a whole to a fraction

Rewrite the whole as a fraction using 3 as the denominator :

3 3 • 3

3 = — = —————

1 3

Equivalent fraction : The fraction thus generated looks different but has the same value as the whole

Common denominator : The equivalent fraction and the other fraction involved in the calculation share the same denominator

Adding fractions that have a common denominator :

2.2 Adding up the two equivalent fractions

Add the two equivalent fractions which now have a common denominator

Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:

4x + 3 • 3 4x + 9

—————————— = ——————

3 3

Equation at the end of step

2

:

(4x + 9)

———————— - 23 = 0

3

STEP

3

:

Rewriting the whole as an Equivalent Fraction :

3.1 Subtracting a whole from a fraction

Rewrite the whole as a fraction using 3 as the denominator :

23 23 • 3

23 = —— = ——————

1 3

Adding fractions that have a common denominator :

3.2 Adding up the two equivalent fractions

(4x+9) - (23 • 3) 4x - 60

————————————————— = ———————

3 3

STEP

4

:

Pulling out like terms :

4.1 Pull out like factors :

4x - 60 = 4 • (x - 15)

Equation at the end of step

4

:

4 • (x - 15)

———————————— = 0

3

4*x/3+3-(23)=0

Step by step solution :

STEP

1

:

x

Simplify —

3

Equation at the end of step

1

:

x

((4 • —) + 3) - 23 = 0

3

STEP

2

:

Rewriting the whole as an Equivalent Fraction

2.1 Adding a whole to a fraction

Rewrite the whole as a fraction using 3 as the denominator :

3 3 • 3

3 = — = —————

1 3

Equivalent fraction : The fraction thus generated looks different but has the same value as the whole

Common denominator : The equivalent fraction and the other fraction involved in the calculation share the same denominator

Adding fractions that have a common denominator :

2.2 Adding up the two equivalent fractions

Add the two equivalent fractions which now have a common denominator

Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:

4x + 3 • 3 4x + 9

—————————— = ——————

3 3

Equation at the end of step

2

:

(4x + 9)

———————— - 23 = 0

3

STEP

3

:

Rewriting the whole as an Equivalent Fraction :

3.1 Subtracting a whole from a fraction

Rewrite the whole as a fraction using 3 as the denominator :

23 23 • 3

23 = —— = ——————

1 3

Adding fractions that have a common denominator :

3.2 Adding up the two equivalent fractions

(4x+9) - (23 • 3) 4x - 60

————————————————— = ———————

3 3

STEP

4

:

Pulling out like terms :

4.1 Pull out like factors :

4x - 60 = 4 • (x - 15)

Equation at the end of step

4

:

4 • (x - 15)

———————————— = 0

3

**Answer:**

3<_x<13/2

**Step-by-step explanation:**